CD32 inhibition and high dose of rhFVIII suppress murine FVIII-specific recall response by distinct mechanisms in vitro - Vollack, Nadine; Friese, Julia; Bergmann, Sabine; Tiede, Andreas; Werwitzke, Sonja (Thrombosis and Haemostasis, 2017)
Development of neutralising antibodies (inhibitors) against factor VIII (FVIII) is a frequent and severe complication of replacement therapy in haemophilia A. Previous data from haemophilia A mouse model demonstrates that both CD32 inhibition and high doses of rhFVIII prevent the differentiation of FVIII-specific memory B cells (MBCs) into antibody secreting cells (ASCs). Here, cellular targets responsible for the suppression of ASC formation by means of CD32 inhibition and high dose of rhFVIII were analysed. We investigated apoptosis on FVIII-specific MBCs using a pan caspases inhibitor, and screened for defects in rhFVIII presentation by analysing T cell release of Th1- and Th2-cytokines in vitro. Although high dose of rhFVIII suppressed ASC formation, cytokine response was not affected. Upon re-stimulation of splenocytes with high dose of rhFVIII, prevention of apoptosis fully restored the FVIII-specific recall response. In contrast, genetic deletion or inhibition of CD32 significantly altered Th1- and Th2-response. CD32 blockade and inhibition of apoptosis resulted in a partial rescue of FVIII-specific ASCs. Normal cytokine secretion could not be restored. In conclusion, suppression of FVIII-specific recall response by CD32 and high doses of rhFVIII is mediated by distinct mechanisms. High dose of rhFVIII induces apoptosis in FVIII-specific MBCs but does not influence FVIII-specific T cell response. CD32 blockade, however, may suppress the FVIII-specific recall response by two ways: i) increasing apoptosis of FVIII-specific MBCs and ii) disturbing FVIII-specific T cell response by modulating presentation of rhFVIII to CD4+ T cells in vitro.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Apoptosis; cytokines; factor VIII inhibitors; haemophilia A / B; immunity